Comparison of clinical safety and efficacy of ultrasound-guided local lauromacrogol injection versus uterine artery embolization in the treatment of caesarean scar pregnancy: a systematic review and meta-analysis - Ziwei Du; Wenjian Xu; Jingyuan Lu; Cheng Li (BMC, 2023)
Abstract Background The aim of this systematic review and meta-analysis was to introduce the relatively novel method of ultrasound-guided local lauromacrogol injection (USG-LLI) followed by dilatation and curettage for caesarean scar pregnancy (CSP) and to investigate the clinical safety and efficacy between uterine artery embolization (UAE) and USG-LLI in the treatment of CSP. Methods The relevant literature and articles about USG-LLI, UAE and CSP published in eight electronic databases were searched to extract the primary outcomes for the selected articles. Review Manager Software(RevMan) V.5.2 was used for quantitative data synthesis and data analysis. Forest plots, sensitivity analysis and bias analysis were also performed on the included articles. Results Of 10 studies included in our search, 623 patients were in the USG-LLI group and 627 patients were in the UAE groups. There were no significant differences between the two groups in terms of success rate, blood loss and time to human chorionic gonadotropin (hCG) normalization. However, USG-LLI group patients than UAE group patients had a shorter duration of hospital stay (mean difference [MD] = -1.97; 95% confidence intervals [CI] -2.63 to -1.31; P < 0.05; I 2 = 95%), shorter restored menses (MD = -4.84; 95%CI -5.78 to -3.90; P < 0.05; I 2 = 95%), and lower complication rates [odds ratio(OR) = 0.21; 95%CI:0.15 to 0.30; P < 0.05]; and cheaper on expenses of hospitalization (MD = -8028.29; 95%CI -10,311.18 to -5745.40; P < 0.05; I 2 = 100%). Conclusions The results demonstrate that USG-LLI is comparable in curative effect and success rates with UAE in the therapy of CSP, but patients in the USG-LLI group seem to have fewer complications rates, shorter duration of hospital stays and lower costs.